2020
DOI: 10.1111/petr.13830
|View full text |Cite
|
Sign up to set email alerts
|

Management and prevention of varicella and measles infections in pediatric solid organ transplant candidates and recipients: An IPTA survey of current practice

Abstract: Background: Varicella and measles infections can be life-threatening after solid organ transplantation (SOT) but may be preventable with live-attenuated vaccines (LAV). Methods: This survey conducted in January 2019 among subscribers of the International Pediatric Transplantation Association listserv aimed to explore the current strategies to prevent and manage both infections in the pediatric SOT population, including recommending LAV after SOT. Results: The answers given by 95 pediatric SOT healthcare worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…In paediatrics, measles and varicella vaccines may be administered earlier than in the standard childhood immunization schedule, at 6 months of age if needed. A recent survey identified this as an ongoing knowledge gap in paediatric transplantation [18]. On the contrary, children younger than 5 are not yet eligible for COVID-19 vaccines as of 1 May 2022, a barrier to pretransplant vaccination against COVID-19 for young paediatric candidates.…”
Section: Hard Stopsmentioning
confidence: 99%
See 1 more Smart Citation
“…In paediatrics, measles and varicella vaccines may be administered earlier than in the standard childhood immunization schedule, at 6 months of age if needed. A recent survey identified this as an ongoing knowledge gap in paediatric transplantation [18]. On the contrary, children younger than 5 are not yet eligible for COVID-19 vaccines as of 1 May 2022, a barrier to pretransplant vaccination against COVID-19 for young paediatric candidates.…”
Section: Hard Stopsmentioning
confidence: 99%
“…A growing body of literature supports that patients with prior transplants may safely receive live, attenuated vaccines under some circumstances [20][21][22]. More than half of the paediatric transplant centres responding to a recent survey were willing to consider these vaccines for transplant recipients, and 21% reported administering them so 'off-label' [18].…”
Section: Key Pointsmentioning
confidence: 99%
“…30 Likewise, in a recent survey of members of the International Pediatric Transplantation Association, only 57% of respondents believe that LAVs should be administered posttransplant, and only 21% have actually administered LAVs to one of their transplant recipients. 31 Both of these studies occurred after the Suresh and AST consensus papers 28,29 were published, suggesting that not only is education required to update transplant providers on new recommendations but also that further studies are needed to obtain additional data to ensure full support from the entire transplant community.…”
Section: Despite Updated Guidelines the Transplant Community Remains ...mentioning
confidence: 99%
“…Another survey by Pettet et al 19 was given in 2019 to the International Pediatric Transplantation Association listserv and discovered that management of live vaccines in solid organ transplant recipients is "not optimal and requires further education." In addition, transplant recipients are generally underimmunized with all vaccines.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A recent study by Kemme et al 18 surveyed 41 Society of Pediatric Liver Transplant centers and found only 29% were offering live vaccines, all of which have different eligibility criteria for live vaccines. Another survey by Pettet et al 19 was given in 2019 to the International Pediatric Transplantation Association listserv and discovered that management of live vaccines in solid organ transplant recipients is “not optimal and requires further education.” In addition, transplant recipients are generally underimmunized with all vaccines 20 . Given all this information, we pursued a quality improvement (QI) approach to increase pediatric liver transplant patient inactive and live vaccination rates and achievement of protective antibody titers.…”
Section: Introductionmentioning
confidence: 99%